Analyse rétrospective de programmes de recherches collaboratives en langues modernes à l’Université de Liège - Jacqueline Beckers; Germain Simons (Recherches en Éducation)
In this paper, we present the outcomes of a study which aims at analysing, in the light of two distinct, though complementary theoretical frameworks, five action-research programmes which we have carried out in the field of foreign language learning/teaching. The first framework, formalized by Desgagné et al (2001), identifies three different steps in collaborative research: ‘cosituation’, ‘coopération’ and ‘coproduction’. The second one, proposed by Pastré (2005), deals with the concept of ‘instrumental’, ‘conceptual’ and ‘identity’ ‘geneses’. First, we briefly present the five collaborative research programmes. Then we explain this double theoretical background. Finally we examine some of the characteristics of the five research programmes through the prism of this theoretical framework and of a vast survey conducted on the teachers and the researchers.